Puerto de carga e industria fluvial (2020)
This document expresses the solutions and strategies that will be developed to respond to the problems that arise in the corridor between Puerto Salgar and Barrancabermeja taking into account the influence of the Magdalena River as the articulating axis of the inherent activities of the corridor, each of these It will be analyzed and contemplated as a means of rescue and evolution for each of these municipalities, which will be stimulated through urban development and architectural projects consistent with the place and its customs